Racial disparities in criminal legal system involvement among New York City overdose decedents: Implications for diversion programs. (1st September 2021) - Mantha, Shivani; Nolan, Michelle L.; Harocopos, Alex; Paone, Denise
Highlights: Criminal legal system diversion is often restricted to those with few prior arrests. Most NYC overdose decedents had been arrested at least once during their lifetimes. Black and Latino overdose decedents were more likely to have ever been arrested. Results show racial disparities in prior felonies at first misdemeanor drug arrest. CLS diversion eligibility is inequitable by race/ethnicity. Abstract: Background: Past studies have identified frequent criminal legal system (CLS) involvement among overdose decedents and highlight the need for connecting individuals at risk of overdose with effective interventions during CLS encounters. While some programs divert individuals at risk of overdose to treatment during CLS encounters, eligibility is frequently restricted to those with limited prior CLS involvement. However, differences by race/ethnicity have not been examined. Objective: We assessed racial disparities in CLS involvement and eligibility for diversion following arrest for misdemeanor drug possession among New York City (NYC) overdose decedents. Methods: We matched death certificates for 5018 NYC residents who died of an unintentional drug overdose between 2008 and 2015 with CLS data and compared CLS involvement by race/ethnicity. We compared prior felony involvement at the first misdemeanor drug arrest by race/ethnicity among 2719 decedents with at least one misdemeanor drug arrest. Results: Higher proportions of Black (86 %, 95 % CI: 83.9, 87.9) and Latino (84 %, 95 % CI: 82.2, 86.0) decedents had ever been arrested than White decedents (73 %, 95 % CI: 71.5, 75.2). At the first misdemeanor drug arrest, Black and Latino decedents were twice as likely as White decedents to have a prior felony conviction, adjusted for age at arrest and gender (RR = 2.08, 95 % CI: 1.71, 2.54 and 2.14, 95 % CI: 1.77, 2.59, respectively). Conclusions: Given racial disparities in CLS involvement among NYC overdose decedents, diversion eligibility is inequitable by race/ethnicity. Diversion programs that restrict eligibility based on prior CLS involvement will have racially disparate effects.